Pentingnya Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Transportasi Ojek Online - Firman Abimanyu; Fianti Irtikha; Ali Ade Setiawan; Ilham Nur Alam Zamzami; Adam Alif Hendrawan; Hananto, Djoko (Philosophiamundi, 2024)
The effect of price and service quality is very important for the continuity of online transportation service companies. Therefore, the purpose of this study is to collect sufficient information about the effect of price and service quality on customer satisfaction of online motorcycle taxi transportation users. The research method used is a literature study that collects several previous studies to determine the effect of price and service quality on online motorcycle taxi transportation. The research results from existing articles show that the effect of price and service quality has a positive and significant effect on customer satisfaction.